If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-x+3=10x-8
We move all terms to the left:
-x+3-(10x-8)=0
We add all the numbers together, and all the variables
-1x-(10x-8)+3=0
We get rid of parentheses
-1x-10x+8+3=0
We add all the numbers together, and all the variables
-11x+11=0
We move all terms containing x to the left, all other terms to the right
-11x=-11
x=-11/-11
x=1
| 4/5y=7/3 | | 75+15x=75 | | 14=g/3+4 | | 4/y=5/8 | | 5/6w=2/3w+3/2 | | t-4=-17 | | (2x-14)(x-28)=0 | | 4h+7h+16=6 | | 3^4x−9=1/243. | | 4+12x=5x-10 | | 4(x+3)+2(3x-5)=-18 | | x+6×=36 | | 3.2x-12.6=-3 | | 3x+4+6x-14=180,x | | 4/5y=21/3 | | 2y^2-3y-54=0 | | -11x+42=141 | | 0=-6x+260 | | x+54=31 | | 9^2x-5=27^3x+2 | | C=200+0.8y-96 | | 80+(4x-2)=2x+50 | | x^2+32x+585=0 | | n/2=5=15 | | 25x^2-90=-81 | | -4n-1=2n=-25 | | 8/5x+3/4x=47/40 | | 22/1=5n | | 2(m+5)+2=3(2m+1) | | 4(5x-3)=40 | | 3(w-6)-2=3(w+2) | | 7.2-4c= |